Diversity versus clonality in carbapenem-resistant A. baumannii: a two-year surveillance study in four intensive care units at a large teaching hospital in Rome, Italy - Mariateresa Ceparano; Valerio Capitani; Giuseppe Migliara; Silvia Rondón; Valentina Baccolini; Alessandra Carattoli; Paolo Villari; Carolina Marzuillo (Antimicrobial Resistance and Infection Control)
Abstract Multidrug-resistant (MDR) Acinetobacter baumannii is a major cause of healthcare-associated infections, which showed a significant increase during the SARS-CoV-2 pandemic, particularly in intensive care units (ICUs). The spread of A. baumannii in these environments is facilitated by contact with contaminated surfaces or infected patients, particularly via the hands of healthcare workers. This study analysed the spread and emergence of specific MDR A. baumannii clusters in four ICUs at the Umberto I teaching hospital in Rome, Italy, between January 2020 and January 2022. Genetic relatedness among A. baumannii isolates was determined by pulsed- field gel electrophoresis (PFGE) and whole- genome sequencing (WGS) performed on representative isolates. A total of 178 A. baumannii isolates, collected from 129 SARS-CoV-2-positive and 49 SARS-CoV-2-negative patients, were classified into 17 PFGE pulsotypes. Overall, 117 isolates belonged to clone A and exhibited an MDR phenotype; all of them belonged to international clonal lineage II. WGS analysis confirmed the presence of outbreaks within and between wards. Reconstruction of the evolutionary distances among isolates identified two locally circulating lineages (LCLs), two distinct clusters, and four outbreaks. Transmission between wards designated for SARS-CoV-2-positive patients and ICUs restricted to SARS-CoV-2-negative patients was also observed. All isolates showed resistance to carbapenems, mainly attributed to the bla OXA−23 gene, and resistance to aminoglycosides, mediated by the armA gene. The study traced epidemic and sporadic infections, yielding valuable information on the implementation of preventive strategies and highlighting the importance of infection control measures to limit the spread of A. baumannii in hospital environments.